2020
DOI: 10.1097/cin.0000000000000685
|View full text |Cite
|
Sign up to set email alerts
|

Status and Influential Factors of Intelligent Healthcare in Nursing Homes in China

Abstract: With the support of the Chinese government, nursing homes have increasingly adopted Internet and intelligent information technology to provide daily healthcare services to residents. However, no research has reported the status of intelligent healthcare in nursing homes. From September 2017 to May 2018, we conducted a survey of 197 nursing homes and collected information on their general characteristics, the intelligent healthcare services provided, the effectiveness of the application products used, and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Similarly, when individuals’ self-perceived ageing degree is relatively positive, the increase in older people’s willingness to use intelligent aged-care products is promoted. For example, Yahui and Yanhua showed that the more positive the self-perception of ageing of older people is, the stronger their willingness to take measures to help their own health status is [ 49 ] and intelligent aged-care products are an important and effective means to help older people improve their health status [ 50 ]. For elderly people with a positive self-perception of ageing, their willingness to use intelligent aged-care products will be stronger.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, when individuals’ self-perceived ageing degree is relatively positive, the increase in older people’s willingness to use intelligent aged-care products is promoted. For example, Yahui and Yanhua showed that the more positive the self-perception of ageing of older people is, the stronger their willingness to take measures to help their own health status is [ 49 ] and intelligent aged-care products are an important and effective means to help older people improve their health status [ 50 ]. For elderly people with a positive self-perception of ageing, their willingness to use intelligent aged-care products will be stronger.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the late development of China's nursing home system, most nursing homes are facing several problems (lack of professional caregivers, security service system to be improved, etc. ), and their services are mostly daily care and medical services, lacking psychological care services (Chen et al, 2021;Meng et al, 2021). Additionally, the closed environment of nursing homes and the lack of social support for residents also influence negatively on the mental health of elderly in nursing homes (Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Because of functional decline and physical diseases, these people frequently have more complex needs and are in greater need of continuous and comprehensive medical care services [3,4]. Hence, daily life service is urgently needed to mitigate inconveniences resulting from the decline of physiological function among older people [5].…”
Section: Introductionmentioning
confidence: 99%